2005
DOI: 10.1084/jem.20042323
|View full text |Cite
|
Sign up to set email alerts
|

Structural and kinetic basis for heightened immunogenicity of T cell vaccines

Abstract: Analogue peptides with enhanced binding affinity to major histocompatibility class (MHC) I molecules are currently being used in cancer patients to elicit stronger T cell responses. However, it remains unclear as to how alterations of anchor residues may affect T cell receptor (TCR) recognition. We correlate functional, thermodynamic, and structural parameters of TCR–peptide–MHC binding and demonstrate the effect of anchor residue modifications of the human histocompatibility leukocyte antigens (HLA)–A2 tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
254
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(274 citation statements)
references
References 57 publications
(80 reference statements)
14
254
0
Order By: Relevance
“…The computational binding free energies have a correlation coefficient of 0.75 compared with experimental results. In our study, we calculated the binding free energy difference values in several TCR-pMHC complex pairs induced by one amino acid substitution at the peptides using PMFScore, and found that the PMFScore results had a good agreement with the experimental results reported previously [28,29] (data not shown). Our data firstly confirmed that the PMFScore can be reliably applied in the case of TCR/pMHC system for rational APL design.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The computational binding free energies have a correlation coefficient of 0.75 compared with experimental results. In our study, we calculated the binding free energy difference values in several TCR-pMHC complex pairs induced by one amino acid substitution at the peptides using PMFScore, and found that the PMFScore results had a good agreement with the experimental results reported previously [28,29] (data not shown). Our data firstly confirmed that the PMFScore can be reliably applied in the case of TCR/pMHC system for rational APL design.…”
supporting
confidence: 69%
“…To test whether the PMFScore method could be applied in the case of the TCR/pMHC complex system, we first calculated the binding free energy differences in several TCR-pMHC complex pairs induced by one amino acid substitution in the peptides using the PMFScore program, and found that the results of the PMFScore analysis corresponded well with the experimental results reported previously [28,29] (data not shown). This makes a possible use of the PMFScore results for obtaining an understanding of the origin of the free energy difference, which was not available from the experimental results.…”
Section: Resultsmentioning
confidence: 57%
“…Crystal structure studies on soluble WT 1G4 TCR protein have demonstrated that amino acid residues 95 and 96 (TS) in the 1G4 CDR3 ␣-chain interact with the NY-ESO-1 peptide in the HLA-A*02-binding groove, whereas CDR2␤ residues interact with the HLA-A*02 ␣2 helix and do not interact at all with the NY-ESO-1 peptide (36). Previously, a crystal structure of a high-affinity 1G4 TCR containing substitutions in both the CDR2␣ and CDR2␤ regions revealed that the orientation of the native CDR3 loops and their specific contacts with bound peptide remained essentially unchanged from the parental wild type (22).…”
Section: Discussionmentioning
confidence: 99%
“…T-cell vaccines) which aim to modulate/ boost the cellular immune response to combat infectious diseases such as AIDs as well as pathologies such as cancer. In Oxford, exploitation of miniaturized and parallelized approaches to protein production and crystallization developed in SPINE has resulted in crystal structures for a series of human MHC class I-peptide-TCR complexes which includes complexes of TCRs recognizing two different tumour antigens (Chen et al, 2005;Hamer et al, in preparation) and TCRs recognizing three different AIDS-virus antigens (StewartJones et al, in preparation; Fig. 5j).…”
Section: Neurological Diseases 421mentioning
confidence: 99%
“…The accumulated experience in Oxford from expression, refolding and crystallization trials on more than 30 TCRs indicates the level of success in going from a pair of -and -chain expression constructs to structure is approximately 33%. The major point of attrition is at the crystallization/optimization of diffraction-quality stage and nanolitre-scale crystallization has played a major role in generating a current portfolio of structures which includes nine TCR-MHC class I complexes (Stewart-Jones et al, 2003;Chen et al, 2005).…”
Section: Standardized Refolding Protocols and Optimized Crystallizatimentioning
confidence: 99%